2011
DOI: 10.1007/s10646-011-0623-3
|View full text |Cite
|
Sign up to set email alerts
|

Conserved toxic responses across divergent phylogenetic lineages: a meta-analysis of the neurotoxic effects of RDX among multiple species using toxicogenomics

Abstract: At military training sites, a variety of pollutants such as hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), may contaminate the area originating from used munitions. Studies investigating the mechanism of toxicity of RDX have shown that it affects the central nervous system causing seizures in humans and animals. Environmental pollutants such as RDX have the potential to affect many different species, therefore it is important to establish how phylogenetically distant species may respond to these types of emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Gust et al noted an enrichment of gene ontology elements related to sensory perception (response to light stimulus, sensory perception of light stimulus, and visual perception) in fathead minnows reared to the F2 generation in a multigenerational exposure to RDX. The behavioral response of the R. pipiens tadpoles to RDX exposure, especially the observed dramatic response to changes in lighting condition, suggests that the neurotoxicant effects of RDX, which have observed across a broad phylogenetic cross‐section of species , also are conserved in this amphibian model.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Gust et al noted an enrichment of gene ontology elements related to sensory perception (response to light stimulus, sensory perception of light stimulus, and visual perception) in fathead minnows reared to the F2 generation in a multigenerational exposure to RDX. The behavioral response of the R. pipiens tadpoles to RDX exposure, especially the observed dramatic response to changes in lighting condition, suggests that the neurotoxicant effects of RDX, which have observed across a broad phylogenetic cross‐section of species , also are conserved in this amphibian model.…”
Section: Discussionmentioning
confidence: 87%
“…Similar lack of significant lethality during exposure to the highest RDX test concentrations, which approached the approximate solubility limit for this compound in water (56 mg/L) [34], was also observed for the freshwater fish O. mykiss, Lepomis macrochirus (bluegill sunfish), and Ictalurus punctatus (channel catfish), whereas a 96-h LC50 value of 15 mg/L was reported for P. promelas [35]. It is known that RDX is a neurotoxicant that affects the central nervous system in fish [36], and it has been demonstrated to cause physiological effects such as seizures in many types of animals as well as humans [36,37]. Lethargy upon RDX exposure also has been noted during rat studies [37].…”
Section: Effects Of Rdx On Tadpole Behaviormentioning
confidence: 85%
“…This hypothesis is supported by at least two lines of evidence obtained in vitro for RDX in the rat amygdala: (1) RDX binds to the picrotoxin convulsant site of the GABA A -R, a Cl − ion channel macromolecular complex, with a significant affinity; and (2) RDX reduces the frequency and amplitude of spontaneous GABA A -R-mediated inhibitory currents and the amplitude of GABA-evoked postsynaptic currents (30). Furthermore, a comparative meta-analysis of RDX impact on gene expression among five phylogenetically disparate species including rat, fathead minnow, earthworm, Northern bobwhite quail and coral shows that all species (even those with no organized nervous system) exhibit toxic effects consistent with a common molecular initiating event, i.e., binding to the GABA A -R or GABA A -like receptor (41). This can be explained by the evolutionary conservation of insect GABA receptors as evidenced by the fact that they share the same allosteric modulatory sites that characterize the mammalian GABA A -Rs (38;42).…”
Section: Discussionmentioning
confidence: 99%
“…Where orthologous pathways occur, pathway-based data can often be extended well beyond the phylogenetic group from which it was derived. For example, hexahydro-1,3,5-trinitro-1,3,5-trizine (RDX) causes seizures and other indicators of neurotoxicity in species as varied as human, rat, quail, and earthworm (Garcia-Reyero et al 2011) (Figure 1). Williams et al (2010) screened for RDX binding to different neurological receptors and found that RDX binds to the picrotoxin binding site in the chloride channel of the γ-aminobutyric acid A (GABA A ) receptor, an interaction associated with the onset of seizures in rats.…”
Section: Use Of Alternative Species and In Vitro Assays In An Aop Framentioning
confidence: 99%
“…Williams et al (2010) screened for RDX binding to different neurological receptors and found that RDX binds to the picrotoxin binding site in the chloride channel of the γ-aminobutyric acid A (GABA A ) receptor, an interaction associated with the onset of seizures in rats. The picrotoxin binding site in the GABA A receptor is highly conserved from humans to earthworms, indicating that binding the GABA A receptor is a likely molecular initiating event in multiple species (Garcia-Reyero et al 2011) (Figure 1). Given the conserved role of GABAergic signaling, results of assays assessing impacts on this pathway are likely to be informative of potential effects across a similarly broad range of species and can provide a reasonable basis for extrapolating mammalian health data to other species.…”
Section: Use Of Alternative Species and In Vitro Assays In An Aop Framentioning
confidence: 99%